A HISTÓRIA E A EXPANSÃO DA EDUCAÇÃO A DISTÂNCIA: UM ESTUDO DE CASO DA UNICESUMAR - Larissa Costa dos Santos (Universidade Federal de Santa Catarina, 2018)
With the advent of the information society, new technology motivated behaviors, attitudes and social relationships, influencing life in society. Education was also one of the areas that got changes driven by technology and one of the forms of education where this reality is more present is the Distance Education (EAD). In view of this, the present study aimed to describe the history and expansion of distance education in the world and in Brazil, and also describe the history and expansion of distance education in a specific case: the higher education institution Unicesumar . For this was carried out qualitative research and data collection was performed by means of literature, document analysis and interviews Unicesumar. Finally, it is noteworthy that the Distance Education in the world, in Brazil and Unicesumar educational institution achieved remarkable progress, but there are still challenges to be overcome due to the fact that there are still places where there is no access to education and also work to combat prejudice mode suffers, as the Distance Education plays a considerable role in relation to democratization of education.